A new species of Pseudogekko (Squamata: Gekkonidae) from the Romblon Island Group, Central Philippines - Siler, Cameron D.; Davis, Drew R.; Diesmos, Arvin C.; Guinto, Faith; Whitsett, Collin; Brown, Rafe M. (Zootaxa, 2016)
We describe a new species of lizard in the genus Pseudogekko from Sibuyan and Tablas islands in the Romblon Island Group of the central Philippines. The new species is diagnosed from other Philippine Pseudogekko by body size and shape, color pattern, and multiple differences in scale characteristics. Pseudogekko isapa sp. nov. has been collected only twice from leaves of shrubs in forested habitat on Sibuyan and Tablas islands. The distinctive new species of false gecko is undoubtedly endemic to this single, isolated island group. The fact that populations of such a distinctive new species of Pseudogekko has escaped notice of herpetologists on the reasonably well-studied and largely protected Sibuyan Island further emphasizes the secretive and forest-dependent habits of Philippine false geckos. These characteristics of their behavior and natural history render them difficult to study and challenge biologists’ efforts to accurately assess their conservation status.